1998
DOI: 10.1051/parasite/1998053231
|View full text |Cite
|
Sign up to set email alerts
|

Echinococcus multilocularisinfection in mice:in vivotreatment with a low dose of IFN-γ decreases metacestode growth and liver fibrogenesis

Abstract: Summary :As no antiparasitic drug is definitively efficient in patients with alveolar echinococcosis, the effects of exogenous IFN-γ on murine Echinococcus multilocularis infection were assessed with regards to the parasite burden, parasite-specific immune responses, and the urinary level of the collagen cross-link pyridinolines. They were analyzed after 3-week treatments with 1 or 5 ug of IFN-γ per day twice a week. The treatment with 1 µg transiently reduced the liver metacestode load, and the metastase weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 12 publications
3
35
0
Order By: Relevance
“…E. multilocularis appears to induce skewed Th2-responses (Emery et al 1996). Based on in vitro and in vivo studies, Th2 dominated immunity was associated with increased susceptibility to disease, while Th1 cell activation through IL-12 (Emery et al 1996), IFNc (Jenne et al 1998 ;Liance et al 1998), TNFa (Amiot et al 1999 and IFNa (Godot et al 2003) was suggested to induce protective immunity in AE Vuitton, 2003). The intense periparasitic granulomatous infiltration indicates an intense host-parasite interaction, and the involvement of cellular immunity in control of the metacestode growth kinetics is strongly suggested by experiments carried out in T cell-deficient mouse strains (Dai et al 2004).…”
Section: H O S T R E S P O N S E T O M E T a B O L I T E S A N D S O mentioning
confidence: 99%
“…E. multilocularis appears to induce skewed Th2-responses (Emery et al 1996). Based on in vitro and in vivo studies, Th2 dominated immunity was associated with increased susceptibility to disease, while Th1 cell activation through IL-12 (Emery et al 1996), IFNc (Jenne et al 1998 ;Liance et al 1998), TNFa (Amiot et al 1999 and IFNa (Godot et al 2003) was suggested to induce protective immunity in AE Vuitton, 2003). The intense periparasitic granulomatous infiltration indicates an intense host-parasite interaction, and the involvement of cellular immunity in control of the metacestode growth kinetics is strongly suggested by experiments carried out in T cell-deficient mouse strains (Dai et al 2004).…”
Section: H O S T R E S P O N S E T O M E T a B O L I T E S A N D S O mentioning
confidence: 99%
“…However, IL-12 treatment has not been evaluated as a therapeutic agent in human AE patients because of potential side-effects. Liance et al (1998) reported that the in vivo treatment of mice with a low dose (1 mg, twice a week for 3 weeks) of IFN-c decreased metacestode growth and liver fibrogenesis. The effect was dosedependent, as the treatment with a higher dose (5 mg, twice a week for 3 weeks) increased the number of metacestodes in the liver.…”
Section: Alveolar Echinococcosis (Ae)mentioning
confidence: 99%
“…IFN-γ is an important activator of macrophages and affects their energetic system (Liance et al 1998). The highest values of IFN-γ were observed after therapy L-MTP-PE + ABZ from weeks 8 to 18 p.i.…”
Section: Discussionmentioning
confidence: 91%